Classification of cancer at prostate MRI: deep learning versus clinical PI-RADS assessment - Schelb, Patrick; Radtke, Jan Philipp; Vollmuth, Philipp; Stenzinger, Albrecht; Hohenfellner, Markus; Maier-Hein, Klaus H.; Bonekamp, David (Radiology, 2019)
To compare the performance of clinical assessment to a deep learning system optimized for segmentation trained with T2-weighted and diffusion MRI in the task of detection and segmentation of lesions suspicious for sPC.
Gesehen am 15.10.2019